The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/gcb.14538
|View full text |Cite
|
Sign up to set email alerts
|

Phenology and productivity in a montane bird assemblage: Trends and responses to elevation and climate variation

Abstract: Climate variation has been linked to historical and predicted future distributions and dynamics of wildlife populations. However, demographic mechanisms underlying these changes remain poorly understood. Here, we assessed variation and trends in climate (annual snowfall and spring temperature anomalies) and avian demographic variables from mist‐netting data (breeding phenology and productivity) at six sites along an elevation gradient spanning the montane zone of Yosemite National Park between 1993 and 2017. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 62 publications
3
22
0
1
Order By: Relevance
“…Although we found no evidence of winter drought carry‐over effects on productivity, we did find population‐specific effects of spring temperature on productivity: Productivity of populations in the montane (sne) and northerly (pnw) regions increased with increasing spring temperature. This finding is consistent with results of multi‐species productivity models applied to MAPS data within the sne region (Saracco et al, ). Productivity was an important contributor to annual variation in population change.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although we found no evidence of winter drought carry‐over effects on productivity, we did find population‐specific effects of spring temperature on productivity: Productivity of populations in the montane (sne) and northerly (pnw) regions increased with increasing spring temperature. This finding is consistent with results of multi‐species productivity models applied to MAPS data within the sne region (Saracco et al, ). Productivity was an important contributor to annual variation in population change.…”
Section: Discussionsupporting
confidence: 91%
“…We hypothesized that F I G U R E 1 Adult male Wilson's warbler in California's Sierra Nevada. Photography credit: Gabriel Gonzalez breeding productivity would depend on drought conditions on the wintering grounds (a carry-over effect) and on spring temperature (Saracco, Siegel, Helton, Stock, & DeSante, 2019;Socolar, Epanchin, Beissinger, & Tingley, 2017) and that adult survival would depend on winter drought and wind conditions during spring migration (Drake, Rock, Quinlan, Martin, & Green, 2014;Huang, Bishop, McKibbin, Drake, & Green, 2017;LaManna, George, Saracco, Nott, & DeSante, 2012). We used transient life table response experiments (LTREs) to decompose variation in population growth rates among vital rate and demographic structure components and to examine how these demographic contributions depended on climate covariates (Koons, Arnold, & Schaub, 2017;Koons, Iles, Schaub, & Caswell, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Studying breeding phenology and productivity in Yosemite National Park from 1993 to 2017, Saracco et al (2019) similarly found that birds benefited from warmer and drier spring conditions. Studying breeding phenology and productivity in Yosemite National Park from 1993 to 2017, Saracco et al (2019) similarly found that birds benefited from warmer and drier spring conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Occupancy rates of most but not all landbirds increased with spring temperature and decreased with spring precipitation. Studying breeding phenology and productivity in Yosemite National Park from 1993 to 2017, Saracco et al (2019) similarly found that birds benefited from warmer and drier spring conditions. Overall bird abundance and diversity could increase if average springtime temperature increases throughout the Rocky Mountains.…”
Section: Discussionmentioning
confidence: 99%
“…In all cases, reproduction and survival are likely to be affected differently by the variation in environmental conditions in each season. For example, warmer springs and summers have been shown to positively influence reproduction in common alpine birds (Meller, Piha, Vähätalo, & Lehikoinen, ; Saracco, Desante, Siegel, Helton, & Stock, ), but to negatively impact the survival of common birds in a wider temperate context (Pearce‐Higgins, Eglington, Martay, & Chamberlain, ). The impact of some environmental conditions can also be delayed to “critical periods” in the seasonal cycle through carry‐over effects.…”
Section: Introductionmentioning
confidence: 99%